Bentuk gambar telapak tangan pada gua-gua Prasejarah di Kabupaten Pangkajene Kepulauan, Sulawesi Selatan - Permana, R. Cecep Eka (Wacana, Journal of the Humanities of Indonesia, 2005)
Cave pictures are one form of human culture found in old sites of dwelling caves of the pre-historical time. Cave pictures can be said to be universal in nature because they are found almost every where in the world, including Indonesia. One form or object of picture frequently found is hand stencils. In Indonesia, beside Kalimantan, the Moluccas, and Irian, it is also found in South Sulawesi, especially in the District of Pangkajene Islands (Pangkep). Twelve caves in Pangkep are studied where 326 hand stencils are found. The hand part, orientation, hand side, number of fingers, size, color, and context are analyzed. The analysis reveals a pattern of hand palms of adults with upward orientation. The analysis also reveals a pattern of hand palms that are brown in color, randomly arranged, within the context of pictures of other hands.